2016
DOI: 10.1007/s00204-016-1727-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance mechanisms in M. tuberculosis: an update

Abstract: Treatment of tuberculosis (TB) has been a therapeutic challenge because of not only the naturally high resistance level of Mycobacterium tuberculosis to antibiotics but also the newly acquired mutations that confer further resistance. Currently standardized regimens require patients to daily ingest up to four drugs under direct observation of a healthcare worker for a period of 6–9 months. Although they are quite effective in treating drug susceptible TB, these lengthy treatments often lead to patient non-adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
196
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(203 citation statements)
references
References 162 publications
(236 reference statements)
1
196
0
6
Order By: Relevance
“…Multidrug resistance in M. tuberculosis , the well-known bacterium that causes tuberculosis (Table 1), is dramatically increasing [56]. The biosynthesis pathways of siderophores produced by M. tuberculosis , mycobactin and the carboxylated form carboxymycobactin (Table 1), are well-understood and have been pharmacologically targeted [57].…”
Section: Using Siderophores To Combat Bacterial Infectionmentioning
confidence: 99%
“…Multidrug resistance in M. tuberculosis , the well-known bacterium that causes tuberculosis (Table 1), is dramatically increasing [56]. The biosynthesis pathways of siderophores produced by M. tuberculosis , mycobactin and the carboxylated form carboxymycobactin (Table 1), are well-understood and have been pharmacologically targeted [57].…”
Section: Using Siderophores To Combat Bacterial Infectionmentioning
confidence: 99%
“…Dentro de ellos la más estudiada es la tuberculosis multidrogorresistente (TB-MDR). 6 La OMS reportó que en promedio en los últimos años 3.3% de la incidencia anual de la tuberculosis corresponde a casos de TB-MDR (un rango que va de 220 000 a 370 000 nuevos casos anuales); 1 este aumento también se reportó en los países antes mencionados. 2,3 Se han encontrado algunos factores que podrían aumentar esta incidencia: tener más de tres campos pulmonares afectados, tener más de ocho meses de tratamiento inicial, tener más de tres episodios de tratamiento antituberculoso, y haber experimentado una falla o un empeoramiento en su último tratamiento, entre otros.…”
Section: Salud Pública De México / Vol 59 No 3 Mayo-junio De 2017unclassified
“…Implica pasar de un modelo centrado en el riesgo a un modelo centrado en la prevención, tomando como base las potencialidades de las personas. 6 Por lo anterior, la escuela, comprendida como un centro de salud y socialización, es un espacio potencial para promover personas resilientes. Por lo tanto, el énfasis de las políticas públicas debería centrarse en el desarrollo de las capacidades humanas, es decir, en una educación para la vida.…”
Section: Salud Pública De México / Vol 59 No 3 Mayo-junio De 2017unclassified
“…[3][4][5] In the past few years, multidrug-resistance (MDR) and extensively drug-resistance (XDR) have become serious problems in TB treatment (over 20% of new infections) 6 and currently many researches focus on finding a way against MDR and XDR for TB treatment. Autophagy is a physiological intracellular mechanism which is responsible for degradation of damaged organelles, misfolded or unfolded protein aggregates, and some of intracellular pathogens.…”
mentioning
confidence: 99%
“…20 Although many investigations have been done so far, the exact mechanism of bacterial recognition and elimination by autophagy (xenophagy) has not been clarified yet. Though, it has been recently reported that ubiquitination, 21 autophagy receptors, and LC3 interaction are involved in this process. 22 It is of great importance to consider that autophagy activation can probably overwhelm the bacterial inhibition of xenophagy and could reestablish its bactericidal role in the host defending mechanisms.…”
mentioning
confidence: 99%